PERANCANGAN SISTEM PENDUKUNG KEPUTUSAN MENGGUNAKAN METODE PROMETHEE - Diyah Ruswanti (Universitas Sahid Surakarta, 2019)
Decision Support System Using the Promethee Method is a solution for selecting partners in an Event Organizer service company. In determining the selection of work partners in this system, it is based on ratings or rankings taken from the calculation results of each criterion. From the results of these calculations, a rating of 1 (one) to 3 (three) is taken, to determine the ranking used 5 (five) criteria. The object of this research is an event organizer service company that will determine its partners. This development will affect the company's consideration of choosing a partner offered by an EO because partners are one of the important parts that play a role in running an event, namely those that provide facilities such as for parties, workshops, seminars, exhibitions, and others.